2013
DOI: 10.1007/s00253-013-4984-9
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and synthesis function of high and low redox potential laccases towards 4-morpholinoaniline and aminated as well as chlorinated phenols

Abstract: Laccases are able to mediate both cleavage and synthesis processes. The basis for this dual reaction capability lies in the property of the enzyme laccase to oxidize phenolic, and to some extent non-phenolic substances, to reactive radicals which can undergo on the one hand separations of small substitutents or large molecule parts from the parent compound and on the other hand coupling reactions with other radicals or molecules which are not themselves oxidizable by laccase. The cleavage of the non-phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…One of the challenges in laccase application for lignin depolymerization as noted by many experts is the fact that the strong polymerization activity of laccase counters the decomposition of lignin by re-polymerizing the degradation products (Roth and Spiess, 2015 ). It was postulated (Hahn et al, 2014 ) that the balance between polymerization and cleavage reactions depend on the structure and redox potential of the laccase, structure and redox potential of the substrate, pH value of the buffer used, incubation temperature, and solvent concentration. Thus, thorough process development is required for directing the reaction into the desired path (Santhanam et al, 2011 ; Singh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges in laccase application for lignin depolymerization as noted by many experts is the fact that the strong polymerization activity of laccase counters the decomposition of lignin by re-polymerizing the degradation products (Roth and Spiess, 2015 ). It was postulated (Hahn et al, 2014 ) that the balance between polymerization and cleavage reactions depend on the structure and redox potential of the laccase, structure and redox potential of the substrate, pH value of the buffer used, incubation temperature, and solvent concentration. Thus, thorough process development is required for directing the reaction into the desired path (Santhanam et al, 2011 ; Singh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This showed that the random formation of phenolic radicals may be channelled into a concerted dimerization. Different reaction conditions may favour polymerization or substitution and cleavage reactions depending on the type of laccase and mediator. No H 2 O 2 or other co‐substrates (except oxygen) are required for the action of laccases, while peroxidases, as used previously, depend on H 2 O 2 by definition.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that laccase-catalyzed oxidation of certain phenolic compounds can result in formation of quinoid products (Lundquist and Kristersson 1985 ). BQ has been reported as a product of oxidation by laccase of 1,4-hydroquinone (Hahn et al 2014 ). Therefore it is noteworthy in this context that while laccase typically has a general positive effect on the fermentability of lignocellulosic hydrolysates, which can be attributed to phenol polymerization, there is at least a theoretical risk with respect to hydroquinones that oxidation reactions to some extent can result in the formation of toxic benzoquinones.…”
Section: Discussionmentioning
confidence: 99%